A theory of child targeting - Olivier Bargain; Olivier Donni (Institute for the Study of Labor (IZA), 2007)
There is a large empirical literature on policy measures targeted at children but surprisingly very little theoretical foundation to ground the debate on the optimality of the different instruments. In the present paper, we examine the merit of targeting children through two general policies, namely selective commodity taxation and cash transfer to family with children. We consider a household that comprises an adult and a child. The household behavior is described by the maximization of the adult's utility function, which depends on the child's welfare, subject to a budget constraint. The relative effects of a price subsidy and of a cash benefit on child welfare are then derived. In particular, it is shown that 'favorable' distortions from the price subsidies may allow to redistribute toward the child. The framework is extended to account for possible paternalistic preferences of the State. Finally, it is shown that, in contrast to the traditional view, well-chosen subsidies can be more cost effective than cash transfers in alleviating child poverty
urn:nbn:de:101:1-2008041560
Keywords: 330; Kinder; Familienleistungsausgleich; Verbrauchsteuer; Steuerbegünstigung; Haushaltsökonomik; Wohlfahrtseffekt; Theorie